New chiral bifunctional iminophosphorane squaramide organocatalysts: synthesis and application in the enantioselective Michael addition. - Camarero Gonzales, Patricia; Franco, Francesca; Raimondi, Laura Maria; Puglisi, Alessandra; Wafda, Rabbani; Benaglia, Maurizio (Synthesis)
The design and the synthesis of new enantiopure squaramide-based bifunctional iminophosphorane catalysts are reported. Starting from readily available starting materials, such as squarate and (S)-tert-leucinol, the synthetic approach involved the construction of a squaramide featuring an azide group, as precatalyst, that is easily stored, not sensible to moisture and very manageable.The chiral iminophosphorane organocatalysts (generated in situ by simple addition of a phosphine to the azide) were tested in the enantioselective Michael addition of -nitro esters to enones, and promoted the reaction in up to 90 % yield and 60 % e.e. The products are valuable precursors of α,α-disubstituted amino acids, important building blocks in the preparation of highly functionalized molecules.The synthesis of an α -methyl substituted proline derivative was demonstrated.